2022
DOI: 10.1002/pon.5907
|View full text |Cite
|
Sign up to set email alerts
|

Coronaphobia: A barrier to ongoing cancer treatment?

Abstract: Introduction Increased stress levels caused by the pandemic might cause delays in cancer treatment. We conducted a survey among cancer patients undergoing treatment to evaluate their psychological wellbeing and treatment adherence during Coronavirus disease 19 (COVID‐19) pandemic. Material and Methods Patients receiving active chemotherapy at a private oncology center between January and May 2021 were included. Healthy volunteers were employees of a district health dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Increased anxiety during the pandemic may result in frequently applying to health institutions or refraining from going to health institutions even when needed [14]. In a study in which a positive correlation was found between hospital anxiety and corona phobia, psychiatric support and encouraging strategies were suggested to prevent the interruption of treatment processes of cancer patients [15]. Psychological counseling has been shown to reduce depression and anxiety scores [16].…”
Section: Discussionmentioning
confidence: 99%
“…Increased anxiety during the pandemic may result in frequently applying to health institutions or refraining from going to health institutions even when needed [14]. In a study in which a positive correlation was found between hospital anxiety and corona phobia, psychiatric support and encouraging strategies were suggested to prevent the interruption of treatment processes of cancer patients [15]. Psychological counseling has been shown to reduce depression and anxiety scores [16].…”
Section: Discussionmentioning
confidence: 99%